Dornase alfa during lower respiratory tract infection post‐lung transplantation: a randomized controlled trial. (4th February 2019) - Tarrant, Benjamin James; Snell, Gregory; Ivulich, Steven; Button, Brenda; Thompson, Bruce; Holland, Anne
Summary: Lung transplant (LTx) recipients are at risk of lower respiratory tract infection (LRTI), while altered physiology may lead to difficulty clearing sputum. Mucoactive agents alter sputum properties and facilitate mucociliary clearance; however, there are no randomized controlled trials (RCTs) studying this post‐LTx. This RCT evaluated the safety and efficacy of nebulized dornase alfa during LRTI post‐LTx. Inpatient adults with LRTI and abnormal sputum following bilateral sequential LTx were eligible. Participants received 5 ml of isotonic saline, or 2.5 ml of dornase alfa, nebulized once daily for 1 month followed by 2 months symptom diary. Primary outcome was lung clearance index (LCI2%). Secondary outcomes included spirometry, quality of life, readmission, length of stay, self‐reported exacerbations, and adverse events at baseline, 1 and 3 months. Thirty‐two participated, 16 in each group, baseline mean (SD) FEV1 % 58 (22), median (IQR) length of stay 7 (5) days, time since LTx 3.49 (6.80) years. There were no significant between‐group differences in LCI2% at any point (1 month mean difference −0.34, 95% confidence interval (CI) −1.57 to 0.89; 3 months −0.76, 95% CI −2.29 to 0.78, favoring dornase alfa). Secondary outcomes were not different between groups. These results do not support the routine use of dornase alfa during LRTI in LTx recipients.